ANALISIS FAKTOR-FAKTO YANG MEMPENGARUHI PERILAKU KONSUMEN BERBELANJA PADA KINGSMART TIMIKA MALL - Natalia Rueng; Nonce Palallo (Jurnal Ekonomi dan Bisnis, 2024)
The purpose of this study is to determine the factors that influence consumer shopping behavior at Kingsmart Timika Mall. The method used in this study is the associative method, data collection techniques used in this study are observation and data collection sheets (questionnaires) using multiple linear regression analysis instruments and using SPSS 25 for windows. The results of the study indicate that Cultural, Social, Personality and Psychological Factors have a significant eflect on consumer behavior in shopping at Kingsmart Timika Mall.